Connection Mark Swap Rupiah To Dollar American States With Inflation Rates In Indonesia: Systematic Literature Review - Alhusna Burhan Ali; Rahmad Dani Wahe; Muchriana Muchran (GoodWill, 2026)
This study aims to analyze the relationship between the Rupiah (IDR) exchange rate against the Dollar American Union (USD) with level inflation in Indonesia through systematic approach Literature Review (SLR). Adopting the PRISMA protocol, a literature search was conducted on the database Scopus for the period 2015-2025. Of the 354 articles identified, 10 met the inclusion criteria for in-depth analysis. synthesis show consistency findings that depreciation Rupiah in a way significant triggering an increase in inflation through the imported mechanism inflation , particularly in energy prices and imported raw materials. Methodological analysis reveals the effectiveness of dynamic models such as ARDL, VAR, and ECM in capturing long-run structural relationships. However, there is a shift significant going to use method machine learning (ELM And NARX (NN) which is proven own precision tall (until 4.57%) in predict trend mark swap during periods of extreme volatility such as the COVID-19 pandemic. Another key finding confirms that the effectiveness of monetary policy in stabilizing prices depends heavily on the interest rate differential . rate differential ) and the institutional credibility of the central bank in managing market expectations.